2018
DOI: 10.1007/s12011-018-1346-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Sulfate and Zinc Glycine Chelate on Concentrations of Acute Phase Proteins in Chicken Serum and Liver Tissue

Abstract: The aim of the study was to determine how inorganic and organic forms of zinc affect the concentrations of C-reactive protein (CRP), serum amyloid A (SAA), alpha-1-acid glycoprotein (α-1-AGP), haptoglobin (Hp), and transferrin (TRF) in the blood and liver tissue of 450 1-day-old Ross 308 chicken. Four experimental groups received one the following: inorganic zinc (ZnSO 4 ), a zinc phytase enzyme supplement (ZnSO 4 -F), organic zinc in combination with glycine (Zn-Gly), or organic zinc supplemented with phytase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 72 publications
1
6
1
Order By: Relevance
“…Even though Zn supplementation is more efficient decreasing the CRP of ill patients, basal levels of CRP can also benefit from Zn supplementation [51]. A study of Jarosz et al reported that chelate of Zn-glycine reduced the basal level of CRP in comparison to Zn sulfate in chickens from 1 to 42 days of age [52]. However, in the results reported here, the basal levels of CRP in dogs were not affected by Zn supplementation.…”
Section: Effect Of Zn Sourcecontrasting
confidence: 51%
“…Even though Zn supplementation is more efficient decreasing the CRP of ill patients, basal levels of CRP can also benefit from Zn supplementation [51]. A study of Jarosz et al reported that chelate of Zn-glycine reduced the basal level of CRP in comparison to Zn sulfate in chickens from 1 to 42 days of age [52]. However, in the results reported here, the basal levels of CRP in dogs were not affected by Zn supplementation.…”
Section: Effect Of Zn Sourcecontrasting
confidence: 51%
“…In the present study, feeding complexed Zn increased circulating SAA post-LPS infusion. Similarly, feeding complexed Zn increased APP production in heat-stressed calves and pigs (Pearce et al, 2015;Abuajamieh et al, 2016), chickens (Jarosz et al, 2019), and transitioning dairy cows (Batistel et al, 2016). Interestingly, Liu et al (2014) demonstrated that Zn deficiency enhances APP production via activating the Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Because CRP is an acute-phase protein in inflammatory responses, and it is stimulated by the presence of both interleucine-1 ( IL-1 ) and interleucine-6 ( IL-6 ), such increase might indicate the development of a local inflammatory process ( Eckersall and Bell, 2010 ). An increase in the concentration of CRP is associated with cell damage caused by pathogens, that within 36 to 48 h postexposure to such stimulus ( Jarosz et al, 2019 ). The reduced growth performance in Bacillus subtilis treatment coincides with the reduction in AMEn and digestible Lys and other amino acids supplied in ratio with Lys in grower and finisher diet.…”
Section: Discussionmentioning
confidence: 99%